Pengaruh Pemilu Umum Terhadap Pelaku Wirausaha Di Kabupaten Lombok Timur 2024 - Rachman, Dedy Febry; Amri, Syaiful (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
General elections are important moments in democracy that not only have an impact on the political order, but also on economic dynamics, including entrepreneurial actors. This research aims to analyze the influence of the general election on entrepreneurs in East Lombok Regency in 2024. The approach used is quantitative with an explanatory design, involving 100 entrepreneurs as respondents selected using the stratified random sampling method. Data was collected through questionnaires, in-depth interviews and document studies. The research results show that elections have various impacts on entrepreneurship. Business sectors such as printing, catering and transportation experienced an average increase in revenue of 15% during the election period, while other sectors faced challenges such as rising raw material prices and market uncertainty. Statistical tests show a significant influence between elections and changes in business activity with p < 0.05. However, this impact was temporary, with an economic slowdown detected post-election. This research indicates the need for stable economic policies during and after the election, including support for negatively affected business sectors. In this way, entrepreneurial actors can more optimally take advantage of economic opportunities that arise during the election and mitigate risks that may occur after the election